Effect Of Combination Of Kegel’s Exercise And Bladder Training In Reducing Urine Inncontinency Episodes In Elderly In Persahabatan Hospital, Jakarta - Sumedi, .; Philip, Koshy; Hafizurrachman, Muhammad (KnE Life Sciences, 2021)
The aging process is defined by the change in the behavior of organisms according to age, which typically results in a decrease in the ability to survive and take care of themselves. This deterioration can, in humans, be influenced by biological, psychological, social, functional and spiritual factors. Urinary incontinence is a condition that typically affects the elderly, and has a huge impact on the daily lives of sufferers. This study considers the effect of a combination of Kegel’s exercises and bladder training in decreasing episodes of urinary incontinence in the elderly. This study uses a Quasi-experimental design with a Pretest-Posttest with Control Group design. The results demonstrate that there are significant differences in the average frequency of urination, hold time and frequency of urinary incontinence between the first and second measurements in the treatment group (each value p=0.0001). The combination of Kegel’s exercise and bladder training is proven to decrease the episode of urinary incontinence in the elderly. Keywords: Kegel’s Exercise, Bladder Training, Urine Inncontinency